Economic autarkeia: the legitimacy of the economic discourse based on the concept of physis (Revista Archai, 2019)
The concept of autarkeia present in the Aristotelian Politics is conceived as inseparable from the end of the city-State, insofar as it is not only constituted for mere living (zen) but for living well (eu zen). This implies a moralization of the state order that allows us to think about the conformation of an economic dimension based on the concept of autarkeia. Taking as a methodological starting point the “dialogical tension zones” device (Mársico, 2010), we will affirm that exists an Aristotelian economic thinking based on three significant concepts of his political philosophy: “self-sufficiency”, “city-State”, “justice” (Polanyi, 1994). Finally, we will affirm that the concept of “natural slavery” aims to guarantee the constitution of an autonomous productive economic order that delegitimizes the federated states’ model of organization (summachia).